PEMBUATAN PROGRAM APLIKASI SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN VENDOR ERP PADA PT SINAR JAYA ABADI DENGAN MENGGUNAKAN METODE WEIGHTED PRODUCT - Reynold Adiputra; Bagus Mulyawan (Fakultas Teknologi Informasi Universitas Tarumanagara, 2018)
Decision Support System (DSS) is a system that can assist a person in making decisions that are accurate and targeted. Many problems can be solved by using SPK, one of which is the selection of ERP vendors. There are several methods that can be used in building a SPK including weighted product (WP). WP is the most widely used method of solving multicriteria problems, such as in SPK ERP vendor selection. This research uses WP method in determining ERP vendor selection. In the selection of ERP vendors, there are 5 criteria that form the basis of decision-making include price, number of user license, warranty period, hardware support value, and implementation time. Price is the cost set by the vendor's owner. The number of user licenses means the number of user licenses that a company will get when purchasing an ERP vendor. Warranty Period means the length of warranty that a company will get when purchasing ERP vendors the length of the warranty period may vary depending on each vendor ERP. Hardware value support is a value used as a hardware reference that will be used to implement ERP from this value can be seen whether hardware can implement ERP or not. While the implementation time means the length of time required to implement ERP on the company. The final result in this research is to help companies to decide which ERP vendors are in accordance with the criteria of the company, so the company can easily take the decision to choose ERP vendors by looking at the results of such research.